2013
DOI: 10.1190/geo2012-0334.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adsorption and Knudsen diffusion on the steady-state permeability of microporous rocks

Abstract: Microporous rocks are being increasingly researched as novel exploration and development technologies facilitate production of the reserves confined in the low-permeability reservoir. The ability to numerically estimate effective permeability is pivotal to characterizing the production capability of microporous reservoirs. In this study, a novel methodology is presented for estimating the steady-state effective permeability from FIB-SEM volumes. We quantify the effect of a static adsorbed monolayer and Knudsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Therefore, upscaling the MD results into a larger scale study is highly necessary. Recently, there have several studies using the LB method, which is considered as a mesoscopic numerical method beyond the microscopic MD, for shale gas flow in the nano/micro-size pores of shale matrix [16][17][18][19][20][21][22][23][24][25] regarding the effects of gas slippage [19-21, 23, 24] and adsorbed layer [18,22,25]. The MD simulation in the present study helps us to understand the adsorption of methane on the pore walls in shale matrix.…”
Section: Upscalingmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, upscaling the MD results into a larger scale study is highly necessary. Recently, there have several studies using the LB method, which is considered as a mesoscopic numerical method beyond the microscopic MD, for shale gas flow in the nano/micro-size pores of shale matrix [16][17][18][19][20][21][22][23][24][25] regarding the effects of gas slippage [19-21, 23, 24] and adsorbed layer [18,22,25]. The MD simulation in the present study helps us to understand the adsorption of methane on the pore walls in shale matrix.…”
Section: Upscalingmentioning
confidence: 95%
“…The effect of the adsorbed gas on the fluid flow can be neglected for conventional rocks with large pore size. However, it should be considered in shale matrix where nanosize pores are dominant [9,[15][16][17][18][19][20][21][22][23][24][25]. Adsorption will affect the fluid flow in a nanosize pore through two mechanisms [16].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, if adsorbed gas is assumed to pre-exists in OM, the intrinsic permeability will increase with the decrease in pressure because the desorbed gas will release some pore space [4]. Nonetheless, no consensus on the volume occupied by adsorbed gas exists in these treatments [14,44,39], also the contribution of the surface diffusion is ignored. In this study, with the introduction of DGM-GMS model, the effect of surface diffusion on K app;om can be easily considered, and based on the assumption that the total flux N total is the sum of N DGM and N GMS , the ambiguity in the adsorption layer thickness can be avoided.…”
Section: Permeability Of Ommentioning
confidence: 98%
“…However the sensitivity of permeability to adsorption and surface diffusion are seldom mentioned. In others, the adsorbed gas is modeled by taking some pore space and therefore reducing the local pore size [27,44,7]. In other words, if adsorbed gas is assumed to pre-exists in OM, the intrinsic permeability will increase with the decrease in pressure because the desorbed gas will release some pore space [4].…”
Section: Permeability Of Ommentioning
confidence: 99%
“…Later, it is confirmed that Klinkenberg's correlation is only first order accurate. Beskok and Karniadakis [18] proposed a second-order correlation by considering the different flow regimes from continuum flow to free molecular flow: [148] firstly used the combination of Beskok and Karniadakis -Florence's correlation along with a 3D incompressible LB model to estimate the for a shale image with a 167nm length in each dimension. In their study, the intrinsic permeability 0 was predicted by standard LBM.…”
Section: Klinkenberg Model Based Lbmmentioning
confidence: 99%